2004
DOI: 10.1111/j.1600-0668.2004.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air pollution by alkylphenols in Tokyo

Abstract: Alkylphenol ethoxylate (APE) are widely used surfactants in both industrial and domestic detergents. When these detergents are released into the environment, APE are biodegraded to the smaller chain ethoxylates and alkylphenols (APs). There are many reports about APs in aquatic environments because of their estrogenic effect on wildlife. In building materials, APs are used as antioxidant for polymer resins such as wall or floor coverings. Although APs has a lower vapor pressure, these agents are released into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…Life-style factors, such as whether shoes are worn indoors or not, may also influence particle size and constituent distributions in house dust. Therefore, we measured whole house dust without sieving in this study in the same manner as that in a number of other studies performed in Japan (Kanazawa et al 2010;Saito et al 2007). However, standardized sampling method adequate for house dust in Japanese residences needs to be established in the future.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Life-style factors, such as whether shoes are worn indoors or not, may also influence particle size and constituent distributions in house dust. Therefore, we measured whole house dust without sieving in this study in the same manner as that in a number of other studies performed in Japan (Kanazawa et al 2010;Saito et al 2007). However, standardized sampling method adequate for house dust in Japanese residences needs to be established in the future.…”
Section: Resultsmentioning
confidence: 97%
“…Kanazawa et al (2010) reported that TBEP, TCEP, and TCMEP were detected at high concentrations (5890, 308, and 291 μg/g, respectively) in the floor dust samples from 41 dwellings in Sapporo. Saito et al (2007) reported that the use of floor polish agents containing TBEP could affect the concentration of TBEP in indoor air. Interestingly, the correlation between the TBEP concentration in the indoor air and house dust samples was the highest for all compounds tested in this study (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…0.50 mm thickness, 3 M, MN, USA), which were set in the first and second layer, respectively, in the sampler, were used as adsorbents. Prior to the sampling of airborne SVOCs, the Empore disks were subjected to ultrasonic cleaning five times for 10 min each by 10 ml of acetone per disk, and the quartz fiber filter disks were heated at 400 • C for 4 h by applying the method by Saito et al [27].…”
Section: Sampling Of Svocsmentioning
confidence: 99%
“…Furthermore, the metabolites of APEs, such as nonylphenol (NP) and octylphenol (OP), exhibit an estrogenic effect at low concentrations [5,17]. They are known as toxic contaminants and can be found in indoor/outdoor air and in the aquatic environment [18,19]. Based on these previous studies, we further examined the effects of EDCs on cell proliferation and the activation of estrogen response element (ERE) in an E2-dependent ovarian cancer cell line, BG-1.…”
mentioning
confidence: 99%